(untitled) (Research, Society and Development, 2022)
The main reasons that hinder the meaningful learning of biological concepts and processes reside in the fragmented and conservative teaching, valuing only the reproduction of knowledge. The methodological practices that favor learning lead to the understanding and assimilation of contents that, because they involve, for example, the microscopic dimension, are difficult to understand. In this context, active methodologies are presented as a teaching-learning principle of recognized effectiveness, with the student as the protagonist of the knowledge development process, with direct, participatory and reflective involvement in all stages of the process. In this context, the present work aimed to use active methodologies to improve the understanding of higher education students about the contents of Embryology, Cytology, Genetics and Molecular Biology. The teachers responsible for the disciplines proposed the activity in the classes of the respective disciplines of Biological Sciences (Bachelor’s Degree) and Biomedicine. The methodological steps used were: bibliographic survey; discussion and approach of the knowledge obtained; selection of materials aimed at raising environmental awareness; model elaboration; use of the didactic models built; write report and presentation. With this experience report, it was observed the excellent interaction and participation of students in the activities developed. Fourteen biological models were obtained, with a notable predominance of models over cells. It was concluded that the teaching of Biology in the light of active methodologies contributes greatly to the resignification of teaching work, aiming at better student performance in relation to the teaching and learning process. In addition, it was an alternative to practical classes that were unfeasible during the pandemic period.